The Dynamics of Water Quality During Culture of Snakehead Fish (Channa striata) in The Aquarium - Dewi Puspaningsih; Eddy Supriyono; Kukuh Nirmala; Iman Rusmana; Cecep Kusmana; Ani Widiyati (Journal Omni-Akuatika)
Intensive culture of snakehead fish used artificial feed with high protein content. The impact of the high use of artificial feed will cause waste that can cause poor water quality and cause fish mortality. The purpose of this research was to know the dynamics of water quality during culture of snakehead fish Channa striata in the aquarium. The test animals used were snakehead fish with a length of 6.90 ± 0.49 cm and weight of 2.57 ± 0.59 g. Fish was maintenanced with a density of 2 fish L-1, 4 fish L-1 and 6 fish L-1. Fish was cultured for four days in an aquarium  with size of  60x40x40 cm3 and water volume  of 20 L. Water quality were observed, i.e, temperature, pH, dissolved oxygen, TAN, nitrite, nitrate, orthophosphate, hardness and alkalinity. The results showed that pH, temperature, hardness, TAN, nitrite, nitrate and ortophosphate were not significantly different between treatments (P>0.05), while dissolved oxygen and alkalinity were showed different significantly (P<0.05). On the fourth day of culture with a density of 4 fish L-1 and 6 fish L-1 has led to water saturation in the culture media. Dynamic of water quality was started on the third day of culture, whereas nitrites could not be converted to nitrate maximally. High levels of nitrate in the snakehead culture indicated that that this culture could be combined with an integrated aquaculture with plants.